Gallium Oxide Nanorods: Novel, Template‐Free Synthesis and High Catalytic Activity in Epoxidation Reactions1. (22nd January 2014) - Lueangchaichaweng, Warunee; Brooks, Neil R.; Fiorilli, Sonia; Gobechiya, Elena; Lin, Kaifeng; Li, Li; Parres‐Esclapez, Sonia; Javon, Elsa; Bals, Sara; Van Tendeloo, Gustaaf; Martens, Johan A.; Kirschhock, Christine E. A.; et al.
Abstract Gallium oxide nanorods with unprecedented small dimensions (20–80 nm length and 3–5 nm width) were prepared using a novel, template‐free synthesis method. This nanomaterial is an excellent heterogeneous catalyst for the sustainable epoxidation of alkenes with H2O2, rivaling the industrial benchmark microporous titanosilicate TS‐1 with linear alkenes and being much superior with bulkier substrates. A thorough characterization study elucidated the correlation between the physicochemical properties of the gallium oxide nanorods and their catalytic performance, and underlined the importance of the nanorod morphology for generating a material with high specific surface area and a high number of accessible acid sites.